Analisis Break Even Point (BEP) Dalam Penetapan Tarif Biaya Dan Kuantitas Pengguna Parkir - Nurhayati, Immas; Rivai, Novan Mushaf (inovator, 2018)
Parking problems at Ibn Khaldun University (UIKA) Bogor are important things that must be learned. There is something that must be evaluated in addition to the parking area, security, and facilities, is about the price rate and quantity of parking users. The model used to measure the price of parking rates and quantity of parking users are the break-even point (BEP). We measure BEP both in price and quantity for cars and motorbikes in July and October 2017. July is the month where all students are on vacation so there is a decrease in parking income. October is the month when all students are active so there is a significant increase in parking income. The results showed that in July, BEP was priced for cars if the quantity of 6101 was Rp. 1,687 and for motorbikes if the quantity of around 15,853 was Rp. 737. BEP in quantity for cars if the price is around Rp. 2000 is 5147 and for motorbikes if the price is around Rp. 1,000 is 12,984. In October, BEP is priced for cars if the quantity of around 12,156 is Rp. 794 and for motorbikes if the quantity of around 32,884 is Rp. 369. BEP in quantity for cars if the price of around 2,000 is 4,827 and for motorbikes if the price is around Rp. 1,000 is 12,700.